Surface characterization and osteoblast-like cells culture on collagen modified PLDLA scaffolds - Más, Bruna Antunes; Cattani, Silvia Mara de Mello; Rangel, Rita de Cássia Cipriano [UNESP]; Ribeiro, Gabrielle de Almeida; Cruz, Nilson Cristino [UNESP]; Leite, Fabio de Lima; Nascente, Pedro Augusto de Paula; Duek, Eliana Aparecida de Rezende (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
Surface modification techniques based on the grafting of chemical functional groups and immobilization of bioactive molecules have been used to improve biocompatibility and clinical performance of bioabsorbable scaffolds in tissue engineering and medicine regenerative applications. This study aimed at developing and characterizing a biomimetic surface to stimulate bone regeneration by a simple and low-cost method of surface biofunctionalization of the poly (L-co-D, L lactic acid)-PLDLA scaffolds. The method was obtained by grafting reaction of carboxyl groups (-COOH) on their surface via acrylic acid (AAc) polymerization process, followed by immobilization of collagen type I (Col). Such approach resulted in a surface morphology markedly modified after treatment, with increase of pores and roughness on PLDLA-AAc surfaces and a network of fibrillar collagen deposition in nonspecific areas of PLDLA-Col surfaces. The cytocompatibility of collagen-immobilized scaffolds was significantly improved in terms of cellular adhesion, proliferation, collagen synthesis and maintenance of osteoblast-like phenotype, indicating, therefore, the fundamental role of collagen protein over the biological interactions that occur by bio-recognition mimetic mechanisms at biomaterials interface. These results indicate that the surface modification method used here may be useful as a strategy to develop biofunctional scaffolds, which provide a more successful clinical application of biomaterials in the tissue engineering field.
Keywords: Bioabsorbable polymers; Collagen immobilization; PLDLA scaffolds; Surface modification; Tissue engineering